Behaviour of ortho-N-Glycoside as Green Corrosion Inhibitors for Tin in 0.5 M Citric Acid - Mohamed Mohamed, Mervate; A. Al-Qadri, Fatima; Alsaiari, Raiedhah; Mohammad Shedaiwa, Iman; Alsaiari, Mabkhoot; Mohamed Musa, Esraa (Asian Journal of Chemistry, 2020)
A bio-nondegradable functional glycoside derivative, viz. ortho-N-glycoside, was extracted from natural cabbage plants and its corrosion inhibition behavior was evaluated in relation to tin in a 0.5 M citric solution. An electrochemical study, using potentiodynamic polarization and scanning electrochemical microscopy (SEM), was conducted to determine corrosion inhibition. The results indicate that ortho-N-glycoside possesses a corrosion inhibition efficiency of 75.83% at a concentration of 0.5 mol L-1. The results of adsorption over the tin surface obeys Langmuir isotherm. The surface and the electrochemical reactivity of the tin samples in the citric acid solutions were examined using the SEM technique. This enable the corrosion type to be demonstrated. The results of the surface analysis be obtained using scanning electron microscopy (SEM).